Estimating the direct Covid-19 disability-adjusted life years impact on the Malta population for the first full year - Sarah Cuschieri; Neville Calleja; Brecht Devleesschauwer; Grant M. A. Wyper (BMC, 2021)
Abstract Background Disability-adjusted life years (DALYs) combine the impact of morbidity and mortality, allowing for comprehensive comparisons of the population. The aim was to estimate the DALYs due to Covid-19 in Malta (March 2020-21) and investigate its impact in relation to other causes of disease at a population level. Methods Mortality and weekly hospital admission data were used to calculate DALYs, based on the European Burden of Disease Network consensus Covid-19 model. Covid-19 infection duration of 14 days was considered. Sensitivity analyses for different morbidity scenarios, including post-acute consequences were presented. Results An estimated 70,421 people were infected (with and without symptoms) by Covid-19 in Malta (March 2020-1), out of which 1636 required hospitalisation and 331 deaths, contributing to 5478 DALYs. These DALYs positioned Covid-19 as the fourth leading cause of disease in Malta. Mortality contributed to 95% of DALYs, while post-acute consequences contributed to 60% of morbidity. Conclusions Covid-19 over 1 year has impacted substantially the population health in Malta. Post-acute consequences are the leading morbidity factors that require urgent targeted action to ensure timely multidisciplinary care. It is recommended that DALY estimations in 2021 and beyond are calculated to assess the impact of vaccine roll-out and emergence of new variants.